A Review of Vanilla planifolia Andrews Horticulture and Curing, Phytochemistry and Quality Evaluation - Gavel, Freya Jemmet; White, Alan; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Vanilla is popular for its flavour and aroma characteristics, although its long and labour-intensive curing period impede its commercial production and result in high commercial prices. This manuscript focuses on the cultivation and processing (curing) of Vanilla planifolia beans, their phytochemistry, and vanillin biosynthetic pathways. We also discuss quality parameters and their analytical determination, with the aim of focussing future studies in this field. Materials and Methods: An extensive literature review was undertaken on the cultivation and curing of vanilla, its phytochemistry, vanillin biosynthetic pathways and quality evaluation. Several search engines including Science direct, Google Scholar and Scopus search engines were used as sources of information. Results: Vanilla planifolia cultivation and processing are lengthy and labour-intensive, resulting in high production costs. This results in high costs to the consumer and relatively low availability. Improvements in these processes may substantially increase the production and quality of the vanilla produced. Several methods have already been incorporated to optimise production. Hand pollination of V. planifolia flowers increases fruiting, and better horticultural practices improve the yield of beans. However, the beans are generally still processed by traditional curing methods. This review highlights processes that may be optimised and discusses the use of biotechnological advances to further enhance the production and quality of vanilla. Conclusion: Commercial vanilla production is growing, with quality vanilla being the second most expensive spice globally. In particular, improvements in Vanilla planifolia horticultural methods and growth conditions, as well as optimising the processing methods, may increase the production and quality of vanilla. Better analytical methods are also required to monitor these improvements.
Keywords: Orchidoideae; Vanilla planifolia; Vanilla; Glucovanillin; Biosynthetic pathway; Biotechnology; Traditional curing; Analytical methods.